EDUCATIONAL POLICIES FOR SUSTAINABLE DEVELOPMENT GOALS: A COMPARATIVE STUDY OF SOCIAL EQUITY INITIATIVES IN SOUTH ASIA AND THEIR GLOBAL RELEVANCE - Ushaque Ahmed (Policy Research Journal, 2025)
The research presented the alignment of South Asian policies on education with the Sustainable Development Goals (SDGs), particularly SDG 4 of Quality Education and SDG 10 of Reduced Inequalities, advancing areas of study. It focuses attention on leveling disparities between rural and urban communities to promote standardized education and equality. By analyzing and comparing various policies in different countries such as Pakistan, India, Bangladesh, Nepal, and Sri Lanka, the study assesses inclusivity, diversity, gender parity, and protection of marginalized communities. This paper also highlights the challenges of financial limitations, cultural barriers, and imbalanced distribution of resources, along with the initiatives like Pakistan’s Ehsaas School Stipend Program, India’s Mid-Day Meal Scheme, and Sri Lanka’s free education policy. The study points out the role of technology in standardizing education quality and access. In conclusion, it was revealed the need for fair allocation of resources, effective policy implementation, and inclusive approaches for sustainable outcomes. Recommendations focus on regional collaboration and utilizing technology to bridge gaps in education.